2D Compound Constructed by Cu3 Units with Mixed Azido and Tetrazole Double Bridges: Synthesis, Structure, and Theoretical Study on Magnetic Properties. Issue 11 (24th July 2015) - Cheng, Min; Lu, Dongmei; Ding, You‐Song; Jia, Qin‐Xiang
Abstract The two‐dimensional (2D) layer CuII compound [Cu3(L)2(N3)4] (1) [L = 2‐amino‐3‐(5‐tetrazole)‐methyate‐N‐pyridine] was synthesized by in‐situ hydrothermal reaction of CuCl2·2H2O, NaN3, and 3‐(5‐tetrazole)‐methyate‐N‐pyridine. The central Cu1 and Cu2 atoms are located in five‐coordinate and six‐coordinate arrangements, respectively. Three CuII ions are linked by mixed double EO (end‐on)‐azido‐tetrazole bridges to give trinuclear CuII clusters, which are further extended by EE (end‐to‐end) azido bridges to form 2D metal‐organic layers. The magnetic exchange interactions in complex 1 were investigated by DFT calculations, and the calculated exchange interaction (J = –849 cm–1) revealed that the double EO‐azido‐tetrazole bridges transmit antiferromagnetic coupling between CuII ions.